Synthesis and antimycobacterial activity of new pyrazolate-bridged dinuclear complexes of the type [Pd(mu-L)(N-3)(PPh3)](2) (PPh3 = triphenylphosphine; L = pyrazolates) - Silva, C. da [UNESP]; Ferreira, J. G. [UNESP]; Mauro, A. E. [UNESP]; Frem, R. C. G. [UNESP]; Santos, R. H. A.; Silva, P. B. da [UNESP]; Pavan, Fernando Rogério [UNESP]; Marino, L. B. [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Netto, A. V. G. [UNESP] (Elsevier B.V., 2014)
Binuclear compounds of the type [Pd(mu-L)(N-3)(PPh3)](2) {L = pyrazolate (1); 3,5-dimethylpyrazolate (2); 4-iodopyrazolate (3); PPh3 = triphenylphosphine} were synthesized and characterized by elemental analyses, infrared and H-1 and P-31{H-1} NMR spectroscopies. The crystal and molecular structures of the complex [Pd(mu-dmPz)(N-3)(PPh3)](2) (2) were determined by single-crystal X-ray diffraction techniques. In vitro antimycobacterial evaluation demonstrated that compound [Pd(mu-Pz)(N-3)(PPh3)](2) (1) displayed a MIC of 8.16 mu M, being more active than some commonly used anti-TB drugs and other Pd(II) complexes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Binuclear Pd(II) compounds; Triphenylphosphine; Pyrazolates; Mycobacterium tuberculosis